Food Hygiene-Sanitation Labels: Is It Important? Analysis of Consumer Attention and Perception Across Age, Gender, Education and Income Groups - Wibowo, Candra Pungki; Syahlani, Ph.D., Suci Paramitasari; Haryadi, Fransiskus Trisakti (Buletin Peternakan, 2024)
The suitability of a product's perceived value to consumers’ needs determines the success of offerings. Food safety labels as product attributes have not yet become a concern for most consumers. This research analyzed consumer attention to NKV certification and perceptions of choosing NKV-certified livestock food products regarding demographic profiles. This research was conducted using a survey and data collection was carried out online via social media between June and August 2023. Respondents were determined using a purposive sampling method with the criteria that they had ever shopped for processed livestock products in the last month and were over 18 years old. A total of 210 data were collected and analyzed using descriptive statistical methods and non-parametric Chi-Square. The results showed that behavior regarding NKV certification is positively related to age, education level, and income variables but not to gender. Further analysis showed that the perception of purchasing NKV products is wise and a first choice is greater in groups with older age and higher education levels. Furthermore, the perception of this purchase has the potential to occur in the group of respondents with an income of at least IDR 1,500,000. Furthermore, NKV has not been considered by all respondents, only 14.28% of respondents thought NKV was an important attribute. This study concluded that demographic variables such as age, education level, and income should be deliberated in profiling the market segment for NKV-certified livestock food products. Behavior to purchase NKV products increases in older age groups, higher levels of education, and income.